Violence, Legitimacy, and Control: The Dynamics of Rebel Rule - Malthaner, Stefan; Malešević, Siniša (PARTECIPAZIONE E CONFLITTO, 2022)
In this paper, we outline four key sociological processes that shape the character of rebel governance. Firstly, we review the complex relationships between rebel rule and state power and look at the ways social order is generated and maintained in the context of rebel governance. Secondly, we explore relational mechanisms of control and the capacity of rebel governance to penetrate the micro social world under its rule. Thirdly, we analyze the social mechanisms through which legitimacy is attained and maintained in a rebelocracy. Finally, we examine the organizational, ideological, and micro-interactional similarities between state- and rebel governance in order to understand how and why some forms of rebel rule transform into the established governmental structures while others fragment or collapse. We argue that in order to further develop our understanding of power relations in civil wars, we need to look at the details of concrete interactions and patterns of relationships at the local level, in which orders of violence, legitimacy and control manifest themselves in everyday life, the lived experiences of those who rule and are ruled, the practices and institutions that emerge from them, and the processes in which they are negotiated.